Epitope‐based DNA vaccine for Alzheimer's disease: Translational study in macaques. Issue 3 (2nd August 2013) - Evans, Claire F.; Davtyan, Hayk; Petrushina, Irina; Hovakimyan, Armine; Davtyan, Arpine; Hannaman, Drew; Cribbs, David H.; Agadjanyan, Michael G.; Ghochikyan, Anahit
Abstract: Background: Clinical trials with passive and active Alzheimer's disease (AD) vaccines suggest that early interventions are needed for improvement of cognitive and/or functional performance in patients, providing impetus for the development of safe and immunologically potent active vaccines targeting amyloid β (Aβ). The AN‐1792 trial has indicated that Aβ‐specific T cells may be unsafe for humans; therefore, other vaccines based on small Aβ epitopes are undergoing preclinical and clinical testing. Methods: Humoral and cellular immune responses elicited in response to a novel DNA epitope‐based vaccine (AV‐1955) delivered to rhesus macaques using the TriGrid electroporation device were evaluated. Functional activities of anti‐Aβ antibodies generated in response to vaccination were assessed in vitro . Results: AV‐1955 generates long‐term, potent anti‐Aβ antibodies and cellular immune responses specific to foreign T‐helper epitopes but not to self‐Aβ. Conclusions: This translational study demonstrates that a DNA‐based epitope vaccine for AD could be appropriate for human clinical testing.